Early vocal ontogeny in a polytocous mammal: no evidence of social learning among sibling piglets, Sus scrofa. (May 2019) - Špinka, Marek; Syrová, Michaela; Policht, Richard; Linhart, Pavel
Abstract : Animals living in social proximity often have similar vocalizations. For many bird and several mammal species, at least part of the vocal similarity is socially learned during ontogeny. Little is known, however, about the ontogenetic origin of vocal similarities among siblings in polytocous mammals. We investigated the influence of social environment and genetic relatedness on the development of acoustic similarities among suckling piglets. To examine whether the common acoustic features are innate or learned by postnatal vocal convergence in the same litter, we cross-fostered piglets among pairs of mother sows immediately after birth and recorded contact calls (grunts) of both the cross-fostered and the noncross-fostered piglets during the suckling period. Acoustic distances of the cross-fostered piglets to their new littermates remained longer than those among noncross-fostered siblings and were as long as those between piglets from different litters. The results show that after being neonatally cross-fostered to another litter, the piglets did not converge acoustically with their new littermates even after several weeks of cohabitation. This is in contrast to the presence of vocal plasticity during the ontogeny of other mammals including other ungulates, indicating that use of vocal learning may vary even in closely related species, perhaps in relation to its adaptive utility within the life history and social organization of the species. Highlights: First study examining ontogeny of vocal sibling similarity in a polytocous mammal. Cross-fostering indicated no evidence for social learning of vocal similarity. Calls of adoptee piglets did not converge towards calls of the host litter. In a situation of low arousal, calls contained more identity and litter information.